(untitled) (Journal Of Educational and Psychological Researches, 2013)
Objective: To know the recent shifts in the decision-making process and theories and stages, techniques and systems affecting it. The need for research coming because of the problems that accompany the decision as a result of the failure Sometimes, poor visualization or the narrow perspective of decision-making than miss the opportunity to choose alternatives or options of the most effective and appropriate to solve a problem. And has received exceptional decision-making process in administrative studies and research to enable the organization to continue its activities and its high efficiency, especially successful that the decision depends on the future, and on a clear vision to achieve the desired goals, here it is occupied decision-making is of extreme importance. The research built on addressing the strategic concepts, cover the destruction of the activities and work of the organization, and give a clear ability and can be guided to achieve harmony and adaptation between ends and means and protect the organization and resources of slipping and deviation The decision-making process is the focus of the administrative process, which is associated with complex realities and values ​​that the organization, which must be careful and cautious in making decisions. And emerged several theories in the development of administrative thought about the decision-making process, including traditional theories and behavioral (humanity), dealt with the development of decision-making process and its stages and the steps that follow it, and administrative problems that require analysis and collection of data required and the sources and factors and criteria that control decision-making and goal achievement. It also touched on the transformations in modern decision-making process, including the transition from totalitarianism to selectivity, and the adoption of scientific method and transform facts and information to the concepts and terminology, and expand decentralized rather than centralized, and overall control to control partial to the distribution of responsibilities and giving flexibility instead of inertia imposed by the central work such as planning, leadership and decision-making and communication that hinder the movement of the organization. The research that the recent developments in the decisions made it possible to overcome the problems associated with decision-making in different environments, and helped in the emergence of technology and electronic management, which played a major role in providing information, data and build information systems and decision support at the levels of the organization’s strategic as well as a shift in thought patterns creative and future outlook in decision-making.